Genesis of the Master Circadian Pacemaker in Mice - Cheng, Arthur H.; Cheng, Hai-Ying Mary (Frontiers in Neuroscience, 2021)
The suprachiasmatic nucleus (SCN) is the central circadian clock of mammals, which is responsible for communicating temporal information to peripheral oscillators via humoral and endocrine signaling, ultimately controlling overt rhythms such as sleep-wake cycles, body temperature, and locomotor activity. Given its heterogeneity and complexity, genesis of the SCN is tightly regulated by countless intrinsic and extrinsic factors. Here, we provide a brief overview on the development of the SCN with special emphasis on mice.